(untitled) (Texas Journal of Philology, Culture and History, 2024)
Today, the reflection of gender ideology from folklore into texts or children’s literature has become an important phenomenon. Critical discourse analysis sheds light on the relations between representatives of the stronger and weaker sex in the selected folklore discourse in order to understand gender ideology. In this way, gender gaps that still exist around us are identified in relation to the selected folklore text; Gender roles are interpreted as a cultural phenomenon